Transcendental convergence between theory perceived and theory in action by the Dean of the College of Education of the Bulacan State University - Borja, Ruben E. II (2012)
This investigation determined the transcendental convergence of the Theories Perceived and the Theories in Action by the Dean of the College of Education in Bulacan State University. The questionnaire was the primary instrument used to gather data which was adapted from the study of Madria (1999) at the University of the Philippines. An interview protocol was also used during focus group discussion. The results showed that the Dean perceived the different theories of management with "high extent" of implementation while the faculty of the college viewed that the actions of the dean in the implementation of those theories are in "moderate extent" only. It means that there is non-convergence between the theory perceived and the theory in action by the dean. After, doing the coding, the researcher came with this category that there is a highly significant convergence in the different theories of management "sees to it that staff members are working to full capacity; "supports informal organization;" and "group's opportunity with the group needs direction. "The transcendental convergence revealed that the Dean is strict to the faculty in accomplishing their workloads, however considerate on the differences of each group and leads the staff in the attainment of the organizational objectives.
Keywords: Transcendentalism